"Such Great Sights": Aestheticizing the Future of Labor in Little Smarty Travels to the Future. Issue 1 (2nd January 2022) - Conn, Virginia L.
Abstract : By considering the aesthetic absence of labor in Ye Yonglie's Little Smarty Travels to the Future, this essay considers the ways in which Ye's illustrated children's book calls readers to help create a utopian post-scarcity society that both patronizes physical labor as beneath the dignity of utopian citizens while also being founded on other classes of labor that it renders invisible. In particular, this essay argues that, by visualizing a future free from labor while refusing to see certain types of labor as part of that freedom, Little Smarty reproduced of some of the very ideological impositions against which it staked a claim, with lasting repercussions for contemporary political messaging.